Influence of Content of Entrepreneurship Training on Performance of Small and Micro Enterprises in the Information and Communication Technology Sector in Nairobi City County, Kenya - Nganu, Margaret; Hannah, Bula (European Journal of Business and Management, 2018)
The objective of the study was to determine the influence of content of entrepreneurship training on performance of the Small and Micro Enterprises in the Information Communication Technology sector in Nairobi, City County, Kenya. Descriptive research design was adopted. Qualitative and quantitative data was collected from a population of 273 small and micro enterprises that successfully received entrepreneurship training prior to the year 2012 from the Information Communication Technology Authority. Systematic random sampling technique was used to select 73 respondents. Descriptive statistics included percentages, frequencies, means and standard deviations while regression analysis was used for inferring meaning to the entire population. The study established a positive significant influence of content of entrepreneurship training on performance. The study recommends broadening of the curriculum of entrepreneurship training beyond the entrepreneurial skills, curriculum development to include technical and managerial skills. Moreover, project management, life skills, legal, international trade, partnerships and collaborations needs to be incorporate in entrepreneurship training programs.
Keywords: Content of entrepreneurship training; Entrepreneurship Training; Performance of SMEs in ICT